Facial types and morphology: A study among Sisaala and Dagaaba adult population in the Upper West Region, Ghana - Raymond Saa-Eru Maalman; Chrissie Stansie Abaidoo; Nancy Darkoa Darko; Joshua Tetteh (Scientific African, 2019)
Craniofacial measurements can be considered to be one of the important tools for determination of the inter-racial and intra-racial morphological characteristics of the head and face. As such, facial indices serve as prominent identification tools in combination with fingerprint patterns for biometric and forensic purposes in the developed world. However in Ghana, although emphasis is placed on the face in the photographic recognition systems used in the issuance of passports, very little information is available on facial phenotypes and its prevalence with respect to ethnicity and sex. Therefore, the aim of this study was to classify the facial types among the Dagaabas and Sisaalas in the Upper West Region of Ghana. In the study, a total of 387 healthy individuals (202 females and 185 males), between 18 and 60 years of age were recruited. The study main finding was that, the males had higher facial height and breadth than females. Facial indices were recorded as 98% and 99% for female and male Dagaabas respectively. The Sisaala male and female participants’ facial indices recorded 102% and 104% respectively. Thus as high as 83% and 72% of the Sisaalas and Dagaabas respectively had hyperleptoprosopic facial type. Keywords: Prosopic, Facial index, Facial types, Facial breadth, Facial height